The four-loop DRED gauge β-function and fermion mass anomalous dimension for general gauge groups - Jack, Ian; Mihaila, Luminita (Journal of high energy physics, 2007)
We present four-loop results for the gauge β-function and the fermion mass anomalous dimension for a gauge theory with a general gauge group and a multiplet of fermions transforming according to an arbitrary representation, calculated using the dimensional reduction scheme. In the special case of a supersymmetric theory we confirm previous calculations of both the gauge β-function and the gaugino mass β-function.